Is complexity tameable? Toward a design for the experience in a complex world. - Carlo Giovannella (Interaction Design and Architecture(s), 2013)
By going to the root of complexity I show that it can be simplified only if apparent. The true complexity - arising from the peculiarities of the laws governing the interaction among n components of a 'natural' system and, as well, from the 'topology' of the latter - requires to deeply re-think the approach to the design: operative framework, expectations, methods, evaluation. Complexity leads also to refocus on: i) the central role and relevance of the person, as core of the experience mediated and supported by technology; ii) the peculiarities of the context; iii) their mutual and unpredictable co-evolution. Accordingly one has to redefine the framework of reference and, as consequence, to empower the individuals through the dissemination of an adequate design literacy.